Analysis of vascularized fibula graft integration to the extracorporeal irradiated bone after replantation: 2-year follow-up - Alves Rezende, Luis Guilherme Rosifini; Penno, Ricardo Alberto Lupinacci; Engel, Edgard Eduard; Mazzer, Nilton (ARCHIVES OF HEALTH INVESTIGATION, 2019)
Background: Major bone segmental defects in oncologic patients continue as a therapeutic challenge to orthopedic surgeons. The few alternatives for its management and the relationship between functional outcome and surgical complications remain among the main restrictions for the indication of different techniques. One of these alternatives is the vascularized fibular graft in association with the creation of a bone channel made from resection of the tumor bone segment after being submitted to the extracorporeal irradiation technique. There is little subject information about long-term follow-up either prospective than retrospective studies. Aim of the study: Retrospective evaluation of vascularized fibular graft union capacity from diaphysis and metaphysis and its integration to the irradiated bone after transplantation. Methods: Eleven patients submitted to extracorporeal irradiation technique and replantation with vascularized fibular graft had their radiographic images on 6, 12 and 24 months of postoperative period evaluated. Results: We observed 45,4% in diaphysis integration in the first year and 72,7% in the second year of follow-up, progressive in the diaphysis focus, and maintenance of the metaphysis focus (33,3%). Conclusion: The fibula has a good capacity for bone integration, showing less influence on the union of the metaphysis portion. Descriptors: Bone Transplantation; Osteosarcoma; Microsurgery; Surgical Oncology. References Myers GJ, Abudu AT, Carter SR, Tillman RM, Grimer RJ. The long-term results of endoprosthetic replacement of the proximal tibia for bone tumours. J Bone Joint Surg Br. 2007;89(12):1632-37. Muscolo DL, Ayerza MA, Aponte-Tinao L, Farfalli G. Allograft reconstruction after sarcoma resection in children younger than 10 years old. Clin Orthop Relat Res. 2008;466(8):1856-62. Puri A, Gulia A, Jambhekar N, Laskar S. The outcome of the treatment of diaphyseal primary bone sarcoma by resection, irradiation and re-implantation of the host bone: extracorporeal irradiation as an option for reconstruction in diaphyseal bone sarcomas. J Bone Joint Surg Br. 2012;94(7):982-88. Hong AM, Millington S, Ahern V, McCowage G, Boyle R, Tatersall M et al. Limb preservation surgery with extracorporeal irradiation in the management of malignant bone tumor: the oncological outcomes of 101 patients. Ann Oncol. 2013;24(10):2676-80. Manfrini M, Vanel D, De Paolis M, Malaguti C, Innocenti M, Ceruso M et al. Imaging of vascularized fibula autograft placed inside a massive allograft in reconstruction of lower limb bone tumors. AJR Am J Roentgenol. 2004;182(4):963-70. Spira E, Lubin E. Extracorporeal irradiation of bone tumor. A preliminary report. Isr J Med Sci. 1968;4(5):1015-19. Krieg AH, Davidson, AW, Stalley PD. Intercalary femoral reconstruction with extracorporeal irradiated autogenous bone graft in limb-salvage surgery. J Bone Joint Surg Br. 2007;89(3):366-71. Ceruso M, Falcone C, Innocenti M, Delcroix L, Capanna R, Manfrini M. Skeletal reconstruction with a free vascularized fibula graft associated to bone allograft after resection of malignant bone tumor of limbs. Handchir Mikrochir Plast Chir. 2001;33(4):277-82. Ortiz-Cruz E, Gebhardt MC, Jennings LC, Springfield DS, Mankin HJ. The results of transplantation of intercalary allografts after resection of tumors. A long-term follow-up study. J Bone Joint Surg Am. 1997;79(1):97-106. Farfalli GL, Aponte-Tinao L, Lopez-Millán L, Averza MA, Muscolo DL. Clinical and functional outcomes of tibial intercalary allografts after tumor resection. Orthopedics. 2012;35(3):e391-96. Aponte-Tinao L, Farfalli GL, Ritacco LE, Averza MA, Muscolo DL. Intercalary femur allografts are an acceptable alternative after tumor resection. Cln Orthop Relat Res. 2012;470(3):728-34.